Glial connexins in glaucoma - Song, Qiuyi; Wu, Xi; Yang, Jiawei; Li, Siqi; Duan, Junguo (Frontiers in Neuroscience, 2025)
Glial cells play a crucial role in maintaining central nervous system (CNS) homeostasis and facilitating the repair of neural tissue following injury. The regulation of neuroglia may serve as a safe and effective strategy for modulating neuroinflammatory responses and restoring glial homeostasis and defense functions. Given that the glial network is composed of connexin (CX) proteins, its neuroprotective role is extensive. Therefore, connexins should be considered as functional “bridges” within this network. This review examines evidence for the active involvement of glial networks in neuroinflammation under both physiological and pathological conditions and summarizes the role of CXs in glaucoma. Finally, potential therapeutic strategies for glaucoma are explored.